2007
DOI: 10.3354/meps337279
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in the role of bottom-up and top-down processes in controlling sandeel abundance in the North Sea

Abstract: The lesser sandeel Ammodytes marinus is a critically important mid-trophic species in the North Sea ecosystem. Seabirds suffered widespread breeding failures in the North Sea in 2004, due to shortages of sandeels, their principal food. Industrial sandeel fisheries also failed in 2003 to 2005. Explaining why sandeels were in short supply is thus critical to understanding and managing the North Sea ecosystem. Sandeel abundance may be controlled 'bottom-up' by food availability or 'top-down' by predation, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 51 publications
0
57
1
3
Order By: Relevance
“…Herring (Clupea harengus) are another oil-rich small pelagic fish taken by guillemots during winter months (Blake et al, 1985;Harris and Bailey, 1992;Sonntag and Hüppop, 2005) and positive correlations between SSTs and herring recruitment and stock biomass have been reported in the Barents Sea (Hjermann et al, 2004). These findings and others indicate that changes in SST and other physical oceanographic variables can have complex food web effects (Durant et al, 2004;Frederiksen et al, 2007). The net impacts on the body condition and hence breeding propensity of piscivorous seabirds may in general be difficult to predict.…”
Section: Discussionmentioning
confidence: 97%
“…Herring (Clupea harengus) are another oil-rich small pelagic fish taken by guillemots during winter months (Blake et al, 1985;Harris and Bailey, 1992;Sonntag and Hüppop, 2005) and positive correlations between SSTs and herring recruitment and stock biomass have been reported in the Barents Sea (Hjermann et al, 2004). These findings and others indicate that changes in SST and other physical oceanographic variables can have complex food web effects (Durant et al, 2004;Frederiksen et al, 2007). The net impacts on the body condition and hence breeding propensity of piscivorous seabirds may in general be difficult to predict.…”
Section: Discussionmentioning
confidence: 97%
“…Also, a decrease in the total landings of this species in the north and the centre of the North Sea has been noticeable. In many ecosystems, sandeel is a key prey fish linking trophic levels (Hain et al 1995, Frederiksen et al 2007). Since forage fish can exert bottom-up control on top predators, variability in the abundance of sandeels in response to fisheries pressure and climate change is likely to affect porpoise populations in the North Sea by increasing the likelihood of starvation (MacLeod et al 2007) and changing their abundance and distribution (Reijnders 1992).…”
Section: Harbour Porpoise Distribution and Prey Species Availabilitymentioning
confidence: 99%
“…data). It has been suggested that herring influence sandeel recruitment in the Shetland population (Frederiksen et al 2007), and sandeel larvae are often found in herring stomachs (Savage 1937, Pommeranz 1981, Last 1989. Hence, poor fit of the model in 2002 may be a consequence of unusually high predation pressure exerted by herring.…”
Section: Does the Model Overlook Something?mentioning
confidence: 99%